Knowledge, Attitude, and Practice regarding Hepatitis B & C and HIV/AIDS among Dentists in Chennai, India - Aditya Jain; Kiran Kumar Pandurangan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Healthcare workers including physicians, dentists, nurses and laboratory workers are considered to be among the groups at the risk of blood-borne pathogen transmission.Dentists are more prone to different infections. Several healthcare centers such as dental clinics lack effective infection control practices. Every Effort is essential to protect both health care workers and patients from HIV exposure in the dental practice as the usual route of transmission is through contact with infected blood or other bodily fluids. Thus, it is necessary to evaluate the Knowledge, Attitude, and Practices (KAP) of dentists regarding infection control and basic principles. A questionnaire of 15 questions was prepared and distributed among a convenience sample of 200 dental practitioners via an online survey platform. The data was collected and analysed. The results of this study demonstrated a satisfactory level of knowledge and attitude of dentists about HBV, HCV and HIV/AIDS infections, but some gaps were observed, suggesting that higher knowledge level of dentists plays a very important role in forming the attitudes and practices regarding patients with HBV, HCV and HIV/AIDS but still a constant update is required to update the knowledge of dentists by attending CDE programmes and conferences related to the dental management of HIV/AIDS and Hepatitis patients.